ANALISIS MAKNA DAN PENGGUNAAN KATA WASHI DAN ORA PADA 37 JUDUL MUKASHIBANASHI - MERRY ZAHROTUL MUFIDAH; ENDANG POERBOWATI (Universitas 17 Agustus 1945 Surabaya, 2018)
In Mukashibanashi, the words Washi and Ora are often used. The word Washi is often used by the elderly people, namely grandfather and grandmother. The word Ora is also often used by young people. Washi and Ora have the same meaning as Watashi. The words Washi and Ora were used in the Edo period. The objectives of this study are to describe the meaning of the words Washi and Ora and to describe the use of the words Washi and Ora. Descriptive method is applied in tnis study. The data analysis procedure is looking for the words Washi and Ora in Mukashibanashi, translating, and analyzing them. After the analysis, it can be concluded that the words Washi and Ora have the same meaning, namely